The past, its revelations and an intricate network of meanings: the process of formation of the city of Lins in the "eyes" of its rotunda - Santos, Rodrigo Amado dos (Risco - Journal of Architecture and Urbanism, 2010)
Studying NOB and its socio-cultural peculiarities, we will realize that structures related to its railroads would spew signs that would show a local identity. Among these, one stands out for its architectural structure: the Rotunda, which had as its objective the maintenance of locomotives. Thus, through a decentralized look on this object, it would be able to amplify railway notions and images, but also, explore histories and social experiences that have settled there, always taking care of seeing it as a "mirror" of narratives that would introduce heterogeneous meanings and looks capable of presenting a new facet to understanding the process that constructed the linense community.